The Conative Function Used in the Advertisement of Covid-19 Vaccine Socialization - I Gusti Ayu Vina Widiadnya Putri; Anak Agung Ayu Dian Andriyani (Pioneer: Journal of Language and Literature, 2022)
This study aims to analyze the conative function used in the covid 19 vaccine socialization advertisement. The objective of this study is to analyze the advertisement of Covid-19 vaccine socialization in conative function. This research is qualitative descriptive research and uses a quantitative approach. This study uses the theory by Jacobson (1980) to analyze data. Then combined with questionnaire data and interviews to find out the respondent's views of the public service advertisements for the Covid-19 vaccine socialization. The results of this study stated that there are several simple sentences used to emphasize that the public service advertisement of the Covid-19 vaccine socialization aims to invite readers to participate in the Covid-19 vaccine program. Questionnaire data stated that as many as 58% of the public were interested and influenced to take part in the Covid-19 vaccine after reading public service advertisements. As many as 78% of readers thought that the public service advertisement was very clear so that it could be easily understood by readers. The use of simple sentence structure makes the sentence a communicative sentence. Then 60% of the public stated that the public service advertisement of the Covid-19 vaccine socialization was effective in providing complete information for readers so they can believe the information.